Does Short-Term Hunger Increase Trust and Trustworthiness in a High Trust Society? - Rantapuska, Elias; Freese, Riitta; Jääskeläinen, Iiro P.; Hytönen, Kaisa (Frontiers in Psychology, 2017)
We build on the social heuristics hypothesis (SHH), the literature on the glucose model of self-control, and recent challenges on these hypotheses to investigate whether individuals exhibit a change in degree of trust and reciprocation after consumption of a meal. We induce short-term manipulation of hunger followed by the trust game and a decision on whether to leave personal belongings in an unlocked and unsupervised room. Our results are inconclusive. While we report hungry individuals trusting and reciprocating more than those who have just consumed a meal in a high trust society, we fail to reject the null with small number of observations (N=101) and experimental sessions (N=8). In addition, we find no evidence of short-term hunger having an impact on charitable giving or decisions in public good game.